Study Of Corrosion Protection Effect of Low Cost Bio Extract- Polymer Coating Material for Mild Steel in Acidic and Marine Environments-a Cost Effective Approach - Athira, R; Poongothai, N; K. Neena, P; G. Sateesh Babu, T; Stanley, John (International Journal of Engineering and Technology, 2018)
The present study was carried out to analyze the performance of an anti-corrosion coating obtained from Carica Papaya extract and PMMA polymer applied on mild steel. This combination was characterized by using FTIR, XRD, Zeta potential measurements and thermogravimetric methods and the presence of major constituents in papaya extract was identified with the functional groups and hetero atoms which Â able to forms a passive film on the metal surface and protects mild steel from corrosion. These results were verified by visual observation and gravimetric method and then confirmed by electrochemical studies such as Tafel and AC impedance studies. Cyclic voltammetry result study showed that papaya extract confers electroactive property to the polymer. Zeta potential and contact angle measurements of this extract and coating material reinforce protection against corrosion due to high potential& more interfacial tension of the metal surface and hydrophobic nature of film, which repulse the water drops on metal surface, thus giving more adherent, non-porous film.Â Â